Praktik Manajemen Risiko di BPRS Harum Hikmahnugraha dalam Perspektif POJK 23/2018 dan SEOJK 03/2023 - Azka Ulqia Purwina; Syarif Hidayatullah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to answer the question regarding how risk management is implemented in Islamic Rural Banks (BPRS), specifically at BPRS Harum Hikmahnugraha, as well as to compare it with the condition of other BPRS that have not yet had an adequate risk management system, such as BPRS “Amanah Sejahtera.” The research method used was field research with a qualitative type, through natural observation and focused interviews with informants from BPRS Harum Hikmahnugraha. The results of the study show that there are still BPRS which have not applied a clear risk assessment system in financing distribution, thus potentially causing problems in the feasibility of customers’ businesses. Meanwhile, at BPRS Harum Hikmahnugraha, risk management policies have been applied in an integrated manner, including risk identification, measurement, monitoring, control, communication, and reporting. The practice is already in accordance with POJK Number 23 of 2018 and SEOJK Number 03 of 2023, with comprehensive coverage including credit, operational, compliance, liquidity, reputation, and strategic risks.